Pembangunan budaya kualiti dalam firma binaan di Indonesia - Rita, Eva (2003)
This study focuses on the development of quality culture in construction firms in Indonesia. The objectives of this study are to identify factors and best activities of each factor that influence the development of quality culture, identify critical factors in the development of quality culture and develop the quality culture model. The study was carried out by using questionnaire survey and supplemented by conducting series of discussions with the •selected parties that directly involved in construction firms. One hundred Indonesian class "A" construction firms were selected as respondents for this study. The data were analysed by using statistical techniques. Validity and reliability test were used to identify factors and the best activities of each factor that influence the development of quality culture. Correlation and regression were used to explain the relationship among factors and to identify critical factors in quality culture development. Path analysis was used in producing the conceptual model. Integration Definition for Function Modelling (IDEFO) method was used to develop the quality culture development model. In conclusion this study has identified eight factors that influence the development of quality culture which include organization structure, communication, motivation, leadership, teamwork, appreciation and recognition, education and training, and also empowerment. This study has identified the critical factors in the development of quality culture in a construction firm. IDEFO model was developed and validated by experts selected from construction sector and other sectors. The development of quality culture model can be used as a guidance in selecting the appropriate strategies for the implementation of a firm's quality culture development.